Head and Neck Necrotizing Fasciitis: Abbreviated SOFA Score Associated With Death and Infection Spread - Kelly L. Vittetoe; Samuel R. Johnson; Teresa A. Benvenuti; Jonathan G. Schoenecker; Stephanie N. Moore‐Lotridge; Sarah L. Rohde (OTO Open, 2023)
Abstract Objective Describe features unique to head and neck (H&N) necrotizing fasciitis (NF) compared to other anatomic regions and specify a prognostic score associated with death and descending necrotizing mediastinitis (DNM). Study Design Retrospective cohort. Setting Tertiary care, level 1 trauma center. Methods A single‐institution database identified 399 confirmed cases of NF between 2006 and 2021, 33 of which involved the H&N. Patients with confirmed H&N NF were sorted into cohorts based on clinical outcomes, with the “poor” outcomes group defined by death and/or DNM. Results Thirty‐three patients with H&N NF were included. Compared to NF of other regions, patients with H&N NF had a significantly lower mortality rate (6.06% vs 20.8%, p = .041) and significantly lower rates of obesity (27.3% vs 63.7%, p < .001) and hypertension (42.4% vs 60.9%, p = .038). Within the H&N group, there were 2 deaths (6.06%) and 8 cases of DNM (24.2%). Diabetes was associated with poor outcomes (p = .047), as was an abbreviated sequential organ failure assessment score for necrotizing fasciitis (nfSOFA) of 2 or greater (p = .015). Conclusion H&N NF is unique among other forms of NF, with a lower mortality rate and lower rates of obesity and hypertension in affected patients. Within the H&N cohort, worse outcomes were associated with diabetes as well as a nfSOFA score of 2 or greater. Timely surgical debridement alongside broad‐spectrum antibiotics remains the mainstay of treatment for NF; however, this simple prognostic score may play a role during the early stages of care for patients with H&N NF.